Identification of an amber nonsense mutation in the rosy516 gene by germline transformation of an amber suppressor tRNA gene. - Doerig, R E (1988)
Seven xanthine dehydrogenase and cross-reacting material negative Drosophila melanogaster rosy stocks were screened for amber and ochre nonsense mutations. Amber and ochre nonsense suppressors were created by site-directed mutagenesis starting from a wild-type tRNA(Tyr) gene. The suppressor tRNA genes were subcloned into a pUChsneo transformation vector providing heat-shock controlled neomycin resistance. The seven rosy stocks were germline transformed with amber and ochre tDNA(Tyr), and the G1 generation was screened for Geneticin resistance. Surviving rosy516 flies transformed with the amber suppressor showed an eye colour intermediate between the original ry516 stock and the wild-type, suggesting that ry516 is an amber nonsense mutant. This was confirmed by sequencing the relevant part of the ry516 gene; the analysis revealed a C-to-T transition in a CAG glutamine codon at nucleotide 1522 of the wild-type rosy gene.